2015
DOI: 10.5505/tjtes.2015.42948
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of triceps-reflecting anconeus pedicle and olecranon osteotomy approaches in the treatment of intercondylar fractures of the humerus

Abstract: BACKGROUND:This study aimed to evaluate the functional outcomes of patients with intra-articular distal humerus fractures treated with triceps-reflecting anconeus pedicle (TRAP) and olecranon osteotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 28 publications
1
13
1
Order By: Relevance
“…The effects of surgical approach on functional outcomes in the treatment of distal humerus fractures have always been a matter of curiosity [18,31,32]. Azboy et al evaluated the functional outcomes of patients with intra-articular DHF treated with triceps-reflecting anconeus pedicle (TRAP) and olecranon osteotomy and they found that TRAP provides better arc of elbow motion with low complication and reoperation rates [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of surgical approach on functional outcomes in the treatment of distal humerus fractures have always been a matter of curiosity [18,31,32]. Azboy et al evaluated the functional outcomes of patients with intra-articular DHF treated with triceps-reflecting anconeus pedicle (TRAP) and olecranon osteotomy and they found that TRAP provides better arc of elbow motion with low complication and reoperation rates [31].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of surgical approach on functional outcomes in the treatment of distal humerus fractures have always been a matter of curiosity [18,31,32]. Azboy et al evaluated the functional outcomes of patients with intra-articular DHF treated with triceps-reflecting anconeus pedicle (TRAP) and olecranon osteotomy and they found that TRAP provides better arc of elbow motion with low complication and reoperation rates [31]. Chen et al compared the triceps-sparing approach with olecranon osteotomy regarding their effects on the functional outcomes of intercondylar fracture and concluded that there was no difference between the functional results obtained by both methods [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Olecranon osteotomy is not as safe as generally considered; its high complication rate should not be underestimated. Articles comparing olecranon osteotomy to paratricipital tend to report higher complication rates, ranging from 45.8% to 55% in patients treated via the olecranon osteotomy versus 27.2% to 40.6% in patients treated via the paratricipital approach [ 11 , 20 , 40 ]. Complications related to osteotomy, such as delayed or non-union, hardware failure, and symptomatic removal of hardware, are prevented when the paratricipital approach is used.…”
Section: Discussionmentioning
confidence: 99%
“…The posterior transolecranon approach used in this study carries several advantages, especially when treating comminuted and complex fractures of the distal humerus. [10][11][12][13][14][15] The primary benefit is maximized visualization of the distal humeral articular surface. In a cadaveric study, Wilkinson and Stanley 16 demonstrated that a transolecranon approach to the distal humerus allows for a 63% and 24% increase to visualization of the humeral articular surface when compared with tricepssplitting and triceps-sparing approaches, respectively.…”
Section: Discussionmentioning
confidence: 99%